Employee Engagement Learning from cross industry-a case study (International Journal of Scientific Research and Management (IJSRM), 2015)
Employee engagement is a key to company performance, leading to positive effects such as higher productivity, improved work quality, and decreased job turnover. Employee engagement is generally the commitment and involvement of the employees towards his or her organization and towards its core values and beliefs. An engaged employee is presumed to be aware of the business context and work dynamics . An engaged workforce is a productive workforce, but getting all of your people on the same page requires effort. Communication builds relationships between all levels of staff, creating an environment of effective collaboration. Empowered employees who feel satisfied in their jobs, dedicated to their work, and confident in their managers, are more likely to be committed to their organization. The focus of the case study is limited to the employee engagement activity by communicating through the use of FM radio